The local management and sustainability of swidden farming in the Villages of Bojongsalam and Sukaresmi, Upper Cisokan Watershed, West Java, Indonesia - IRA ROBIBATUL CHOIR; JOHAN ISKANDAR; PARIKESIT PARIKESIT; RUHYAT PARTASASMITA; TEGUH HUSODO; JOKO KUSMORO; ERRI NOVIAR MEGANTARA (Biodiversitas Journal of Biological Diversity, 2018)
Choir IR, Iskandar J, Parikesit, Partasasmita R, Husodo T, Kumoro J, Megantara EN. 2018. The local management and sustainability of swidden farming in the Villages of Bojongsalam and Sukaresmi, Upper Cisokan Watershed, West Java, Indonesia. Biodiversitas 19: 1054-1065. In the past, the swidden farming (huma or ladang) system had been predominantly practiced by village people of West Java. Nowadays, however, the huma farming has rarely been practiced by the village people of West Java due to the government policy, and environmental and socioeconomic changes. The local community who reside in the Villages of Bojongsalam and Sukaresmi, the upper stream of Cisokan, West Java, Indonesia, has still practiced both the wet rice field (sawah) and the huma farming in the private land, production forest of a state-owned forest company (Perhutani), and a state-owned electric company (PLN) project land. Recently some areas of the huma land have been used for the project of the Hydroelectric Power Plant of the Upper Cisokan Pumped Storage (UCPS). As a result, the sustainability of huma system of the local people of Bojongsalam and Sukaresmi has been seriously disturbed. The aims of this study were to elucidate the local management of the huma farming systems that are undertaken by local people of Bojongsalam and Sukaresmi Villages, and to analyze the sustainability of the huma farming of local people of Bojongsalam and Sukaresmi Villages as affected by the UCPS Hydroelectric Power Plant project. The qualitative method was used, while several techniques of collecting the primary data, namely observation and in-depth interviews with informants were applied in this study. The results of study showed that the local management of the huma farming has been annually undertaken by the local people of Bojongsalam and Sukaresmi, including deciding the location of huma plot, preparing the land (cutting shrubs and burning vegetation biomass), planting rice (ngaseuk) and other annual crops, weeding (ngored) and providing chemical fertilizers (mupuk), controlling pests, harvesting rice (dibuat), and fallowing land. Based on analysis of the emergent properties of the agroecosystem of huma farming, it can be predicted that productivity, stability, equitability, and sustainability of the huma farming systems of Bojongsalam and Sukaresmi Villages tend to be low in the near future due to the impact of UCPS Hydroelectric Power Plant project.